Transferring Human Impedance Regulation Skills to Robots - Ajoudani, Arash; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book introduces novel thinking and techniques to the control of robotic manipulation. In particular, the concept of teleimpedance control as an alternative method to bilateral force-reflecting teleoperation control for robotic manipulation is introduced. In teleimpedance control, a compound reference command is sent to the slave robot including both the desired motion trajectory and impedance profile, which are then realized by the remote controller. This concept forms a basis for the development of the controllers for a robotic arm, a dual-arm setup, a synergy-driven robotic hand, and a compliant exoskeleton for improved interaction performance.
Introduction -- On the Role of Compliance and Geometry in Mechanical Stability of the Humans and Robots -- Teleimpedance Control of a Robotic Arm -- Human-like Impedance Control of a Dual-Arm Manipulator -- Teleimpedance Control of a Robotic Hand -- Teleimpedance Control of a Compliant Knee Exoskeleton.
Keywords: Control engineering; Robotics; Automation; Artificial intelligence; Computational intelligence; Control, Robotics, Automation; Artificial Intelligence; Computational Intelligence; Control and Systems Theory